GLICOALCALOIDES DOS FRUTOS DO SOLANUM FLACCIDUM VELL - Almeida, Adelia Emilia de [UNESP]; Rocco, M. A. [UNESP] (My University, 1995)
From the fruits of Solanum flaccidum Vell, two glycoalkaloids (solamargine and solasonine) and one aglycone (solasodine) were isolated and identified.
Glycoalkaloids from the fruits of Solanum flaccidum Vell
Keywords: solamargine; Solanum flaccidum Vell; solasodine; solasonine; steroidal glycoalkaloids; solanum alkaloid; unclassified drug; drug identification; drug isolation; fruit; nonhuman